Syaria’s Maqashid Implementations in Resources Related to the Green Economy - Kurniasih, Dwi (Master of Sharia Economics Program, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Responsible and efficient use of natural resources is vital to the long-term sustainability of our planet. Sustainable Resource Management involves balancing the needs of economic development, social welfare, and environmental protection. Where in practice the management of natural resources is the practice of the concept of the fulfilment of basic human needs framed in the “Maqahid Sharia’ah”. For this research using the method of research used is by using the qualitative approach of library research, and method of collection of data literature review forms of journals and related documents. Studies have shown that the concept of the so-called